Sustainability of Boots.com's growth Strategy as an application service provider (ASP) from services perspective for better engagement of customers, suppliers and partners - Cherian, Bijoy (2008)
As per the MBA project curriculum, our team of three [3] members were assigned a consulting group project by Boots.com. Also we were assigned to write an individual report critically reviewing the key aspects of the group project. As assigned in the group project we investigated the growth strategies for Boots.com in the online market by employing the product line expansion strategy. Boots.com is an specialist online retailer in Health and Beauty(H&B) market, under the current market dynamics Bots.com is facing tough competition in the online business. For the same Boots.com current focus is expanding the online product line for sustaining growth. However, I choose to consider the services perspective of Boots.com since it was not the key area of focus at the moment. And the challenge of sustaining growth could be considered not only from product line expansion but also from online services perspective. So that Boots.com can be a specialist Application Service Provider (ASP) in H&B online market. This report comprises of six [6] chapters. The introduction chapter is followed by, literature review discussing the theoretical aspects of strategy, services marketing and technology. Further followed by the research methodology by focus on the customer activity cycle and results and findings derived from the research methodology conducted. Then, we analyse Boots.com internally and externally from strategic perspectives which is followed by proposed business model for Boots.com for creating new markets through services approach. Finally, the report showcases the conclusions and recommendations for Boots.com's proposed business model.